PEMANFAAATAN FOOD RECYLING PADA KITCHEN SECTION HARRIS RESORT WATERFRONT KOTA BATAM - Iga Maidini Mawardi; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Covid-19 has created a very significant new change in the world of tourism where freedom of travel can no longer be as free as it used to be in the days before the pandemic, tourists cannot travel without health care. Currently, one of the resorts that is still surviving during the pandemic is Harris Resort Waterfront Batam. It is one of the four-star resorts in Batam that has good and wise use of Food Recyling, this has an impact on food costs. Harris Resort Waterfront is still in a stable condition. Food recycling is food ingredients, both processed and unprocessed, that are thrown away in vain, while there are still many uses that can be taken from food ingredients that can be reprocessed to reduce costs. Therefore, this study aims to determine the use of Food Recyling in the Kitchen Section of Harris Resort Waterfront Batam. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and documentation. Utilization of Food Recyling that is carried out is Product Recycling Terms of Reprocessing Utilization Produced by Reprocessing Based on the results of research that has been carried out, for the overall results of observations and interviews, it can be concluded that the Utilization of Food Recyling in the Kitchen Section of Harris Resort Waterfront Batam has been running according to the procedure which has been done Keywords: Hotel, Food Recycling